(1-Bromovinyl)-MIDA boronate: a readily accessible and highly versatile building block for small molecule synthesis - Woerly, Eric M.; Miller, Jonathan E.; Burke, Martin D. (Tetrahedron, 2013)
Iterative cross-coupling represents a potentially general approach for the simple, efficient, and flexible construction of a wide range of functional small molecules. In this context, (1-bromovinyl)-N-methyliminodiacetic acid (MIDA) boronate is a very useful building block for small molecule synthesis. This compound can serve as a starting material for the preparation of a wide range of 1,1-disubstituted olefin-containing MIDA boronates. This compound can also be used for the iterative cross-coupling-based synthesis of various 1,1-disubstituted olefin-containing targets. Collectively, these results contribute to the expanding generality of the MIDA boronate platform. [Display omitted]